Can Robotic Systems Promote Self-Disclosure in Adolescents with Autism Spectrum Disorder? A Pilot Study - Kumazaki, Hirokazu; Warren, Zachary; Swanson, Amy; Yoshikawa, Yuichiro; Matsumoto, Yoshio; Takahashi, Hideyuki; Sarkar, Nilanjan; Ishiguro, Hiroshi; Mimura, Masaru; Minabe, Yoshio; Kikuchi, Mitsuru (Frontiers in Psychiatry, 2018)
Research suggests that many individuals with autism spectrum disorder (ASD) often demonstrate challenges providing appropriate levels of information during conversational interchanges. Considering the preference of individuals with ASD, and recent rapid technological advances, robotic systems may yield promise in promoting certain aspects of conversation and interaction such as self-disclosure of appropriate personal information. In the current work, we evaluated personal disclosures of events with specific emotional content across two differing robotic systems (android and simplistic humanoid) and human interactions. Nineteen participants were enrolled in this study: 11 (2 women and 9 men) adolescents with ASD and 8 (4 women and 4 men) adolescents with TD. Each participant completed a sequence of three interactions in a random order. Results indicated differences regarding comfort level and length of disclosures between adolescents with ASD and typically developing (TD) controls in relation to system interactions. Specifically, adolescents with ASD showed a preference for interacting with the robotic systems compared to TD controls, and demonstrated lengthier disclosures when interacting with the visually simple humanoid robot compared to interacting with human interviewer. The findings suggest robotic systems may be useful in eliciting and promoting aspects of social communication such as self-disclosure, for some individuals with ASD.